Quality of life of coronary artery disease patients after the implementation of planning strategies for medication adherence - Laura Bacelar de Araujo Lourenço; Roberta Cunha Matheus Rodrigues; Thaís Moreira São-João; Maria Cecilia Gallani; Marilia Estevam Cornélio (Universidade de São Paulo, 2015)
OBJECTIVE: to compare the general and specific health-related quality of life (HRQoL) between the Intervention (IG) and Control (CG) groups of coronary artery disease patients after the implementation of Action Planning and Coping Planning strategies for medication adherence and to verify the relationship between adherence and HRQoL.METHOD: this was a controlled and randomized study.RESULTS: the sample (n=115) was randomized into two groups, IG (n=59) and CG (n=56). Measures of medication adherence and general and specific HRQoL were obtained in the baseline and after two months of monitoring.CONCLUSION: the findings showed that the combination of intervention strategies - Action Planning and Coping Planning for medication adherence did not affect the HRQoL of coronary artery disease patients in outpatient monitoring.